What and how about competitive benchmarking (2011)
Most of the domestic industries In Nigeria lag behind their foreign competitors when it comes to cost and quality. People turn to the low price and often higher quality of imported goods. This paper suggests that benchmarking could be used to match and even exceed the competition. Based on the experience of companies in the industrialized world that have successfully used benchmarking to overcome adversity and have emerged stronger, the paper suggests that the same success could be achieved by our domestic industries. The description of the benchmarking process, the guidelines and framework for its application and some of the implementation problems are discussed